Jendela Kata, Pintu Logika: Studi Korelasi Perkembangan Kognitif dan Bahasa terhadap Kesejahteraan Psikologis Anak Usia Dini - Dieni Febrianti Zahra; Risbon Sianturi; Taopik Rahman; Livia Fitriany; Silva Nurul Aulya; Siti Nur Padilah (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study examines the relationship between language development as a "window to words," cognitive function as a "door to logic," and psychological well-being in early childhood. The study used a meta-synthesis approach to 37 interdisciplinary scientific sources published between 2022 and 2026. The analysis shows that language skills play a crucial role in helping children express and manage emotions, while cognitive development serves as a foundation for understanding and organizing the surrounding reality. An imbalance in any of these aspects can lead to decreased emotional resilience, characterized by anxiety, difficulty regulating oneself, and difficulties adapting. These findings emphasize that psychological 1 well-being is not simply the end result of the developmental process, but rather a crucial foundation formed through the integration of comprehensive language and cognitive development